A Study Of The Mechanical Properties Of Crumb Rubber Lightweight Foamed Concrete With Density Of 1100-1200 Kg/ M3 - Oon, Kel Lee (2020)
For the past few decades, the disposal of waste tyres has become a serious environmental problem as a huge amount of scrap tyres are being generated worldwide. Many researchers had been studying this issue and actions had been made. It appears that recycling scrap tyres were the best and most effective solution for disposing of this material due to its economic and ecological advantages. This study was carried out to study on the feasibility of using crumb rubber particles as a partial replacement of fine aggregates in lightweight foamed concrete. Besides, it could be a benchmark for future studies in this field to accommodate a better and more sustainable production of building insulators. The mechanical properties such as the compressive strength, tensile strength and flexural strength of crumb rubber lightweight foamed concrete were tested based on the ASTM standards. Two sizes of crumb rubber particles were used in this study, namely, the granular crumb rubber (1 - 4 mm) and powdered crumb rubber particles (40 mesh). This study has proven that the utilization of granular and powdered crumb rubber in lightweight foamed concrete could affect the mechanical properties like the compressive, splitting tensile and the flexural strength. The highest compression and tensile strengths of 20 % granular crumb rubber lightweight foamed concrete (GCLFC) were reported with a value of 2.930 MPa and 0.399 MPa while the highest flexural strength obtained from 10 % of crumb rubber replacement was 2.248 MPa. The mechanical strength of GCLFC had increased by 10.27 % (compressive), 21.65 % (splitting tensile) and 2.97 % (flexural) compared with the controlled mix specimens. However, as the crumb rubber proportion of GCLFC increases more than 20 %, a significant reduction of mechanical strength was noticed. On the other hand, the powdered crumb rubber lightweight foamed concrete (PCLFC) has the highest compressive and splitting tensile strength at 70 % of crumb rubber proportion with the values of 3.227 MPa and 0.533 MPa whereas the highest flexural strength is at 80 % of crumb rubber proportion with a value of 2.829 MPa. In a nutshell, PCLFC has better improvement in the mechanical strength as it has increased by 3.01 % to 33.87 % (compressive), 2.44 % to 62.5 % (splitting tensile) as well as 6.7 % to 29.6 % (flexural) compared to the controlled mix.